A Randomized, Placebo‐Controlled Phase III Extension Trial of the Long‐Term Safety and Tolerability of Anifrolumab in Active Systemic Lupus Erythematosus - Kalunian, Kenneth C.; Furie, Richard; Morand, Eric F.; Bruce, Ian N.; Manzi, Susan; Tanaka, Yoshiya; Winthrop, Kevin; Hupka, Ihor; Zhang, Lijin (Jinny); Werther, Shanti; Abreu, Gabriel; Hultquist, Micki; et al. (Arthritis & Rheumatology, 2023)
Objective To explore long‐term safety and tolerability of anifrolumab 300 mg compared with placebo in patients with systemic lupus erythematosus (SLE) who completed a Treatment of Uncontrolled Lupus via the Interferon Pathway (TULIP) trial and enrolled in the placebo‐controlled 3‐year long‐term extension (LTE) study (ClinicalTrials.gov identifier: NCT02794285). Methods In the blinded LTE study, patients continued anifrolumab 300 mg, switched from anifrolumab 150 mg to 300 mg, or were re‐randomized from placebo to receive either anifrolumab 300 mg or to continue placebo, administered every 4 weeks. Primary comparisons in the LTE study were between patients who received anifrolumab 300 mg or placebo throughout the TULIP and LTE studies. For rare safety events, comparisons included patients who received any anifrolumab dose during TULIP or LTE. When exposure differed, exposure‐adjusted incidence rates (EAIRs) per 100 patient‐years were calculated. Results In the LTE study, EAIRs of serious adverse events (SAEs) were 8.5 with anifrolumab compared with 11.2 with placebo; likewise, EAIRs of AEs leading to treatment discontinuation were 2.5 versus 3.2, respectively. EAIRs of non‐opportunistic serious infections were comparable between groups (3.7 with anifrolumab versus 3.6 with placebo). Exposure‐adjusted event rates of COVID‐related AEs, including asymptomatic infections, were 15.5 with anifrolumab compared with 9.8 with placebo. No COVID‐related AEs occurred in fully vaccinated individuals. EAIRs of malignancy and major acute cardiovascular events were low and comparable between groups. Anifrolumab was associated with lower cumulative glucocorticoid use and greater mean improvement in the SLE Disease Activity Index 2000, compared with placebo. Conclusion This LTE study represents the longest placebo‐controlled clinical trial performed in SLE to date. No new safety findings were identified in the LTE study, supporting the favorable benefit–risk profile of anifrolumab for patients with moderate‐to‐severe SLE receiving standard therapy.